2016
DOI: 10.1017/s0007114516003755
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of empirical indices to assess the insulinaemic potential of diet and lifestyle

Abstract: The glycemic and insulin indices assess postprandial glycemic and insulin response to foods respectively, which may not reflect the long-term effects of diet on insulin response. We developed and evaluated the validity of four empirical indices to assess the insulinemic potential of usual diets and lifestyles, using dietary, lifestyle and biomarker data from the Nurses’ Health Study (NHS, n=5,812 for hyperinsulinemia, n=3,929 for insulin resistance). The four indices were: the empirical dietary index for hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
175
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 106 publications
(188 citation statements)
references
References 50 publications
12
175
1
Order By: Relevance
“…Up until the development of the DII, all dietary indices fell into one of three categories: (1) those based on dietary recommendations such as the Healthy Eating Index-2010 (HEI-2010) [ 51 ], or the Alternative Healthy Eating Index (AHEI) [ 52 ], both based on the US Dietary Guidelines or the Dietary Approaches to Stop Hypertension (DASH) [ 53 ], which was promoted by the National Heart, Lung, and Blood Institute; (2) those related to adherence to a particular foodway or cuisine such as the Mediterranean Dietary Index (MDI) [ 54 ]; or (3) those derived from a particular study using some kind of regression technique such as principal components analysis or reduced rank regression [ 55 ]. These indices have been examined with CVD incidence and mortality as outcome in the past [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Up until the development of the DII, all dietary indices fell into one of three categories: (1) those based on dietary recommendations such as the Healthy Eating Index-2010 (HEI-2010) [ 51 ], or the Alternative Healthy Eating Index (AHEI) [ 52 ], both based on the US Dietary Guidelines or the Dietary Approaches to Stop Hypertension (DASH) [ 53 ], which was promoted by the National Heart, Lung, and Blood Institute; (2) those related to adherence to a particular foodway or cuisine such as the Mediterranean Dietary Index (MDI) [ 54 ]; or (3) those derived from a particular study using some kind of regression technique such as principal components analysis or reduced rank regression [ 55 ]. These indices have been examined with CVD incidence and mortality as outcome in the past [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…8,13,15,30,32 Alcohol consumption can also interfere with the breakdown and absorption of other nutrients, and alcohol metabolism generates reactive oxygen species which can damage DNA, proteins, and lipids. 30 Moderate alcohol empirically lowers inflammatory markers and C-peptide, [33][34][35] and a short-term randomized clinical trial observed a benefit of alcohol on insulin parameters. 36 A 2017 study of the effects of moderate alcohol consumption in rats observed that moderate levels of alcohol intake did not elevate biological risk factors for CRC development and may provide beneficial effects through reduced inflammation and lower DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…One advantage of the empirical hypothesis-oriented dietary patterns is their focus on a specific biological pathway linking diet and disease outcomes. Dietary indices have been developed with inflammation [24]**[17, 74] and insulin response [25]** as the central theme in their development. Association of these indices with disease incidence indicates that inflammation or insulin response, respectively may be mediating the development of the disease, e.g., dietary inflammatory potential has been found to be associated with colorectal cancer risk in several studies [43]*[75].…”
Section: Discussionmentioning
confidence: 99%
“…The validity of the score relative to the underlying hypothesis is evaluated in independent study populations, and the dietary pattern score is then derived and used in different study populations (in the same manner as a priori patterns) to examine its association with disease risk [24, 25]**. For example, Tabung et al , used reduced rank regression [26] to develop an empirical dietary inflammatory pattern (EDIP) score [24]**, and stepwise linear regression analyses to develop empirical indices to assess the insulinemic potential of diet and lifestyle [25]**. These indices may then be used to examine associations with diseases whose development is hypothesized to be mediated through the inflammatory or insulin response pathways respectively.…”
Section: Methodsmentioning
confidence: 99%